Analisis Penyebab Keterlambatan Produksi Departemen AD 2 PT. X - Jeanny Pontjoharyo; Tanti Octavia (Jurnal Titra, 2018)
PT. X is a company that produces cosmetic packaging based on make to order system. This company consist of five departements which one of them is assembly and decorating 2 (AD 2). AD 2 Department causes 28% of 59% production delay. Production delay is caused by two factors, these are internal factors and external factors. Effectiveness and level of rejection included in internal factors. Low effectiveness occurs due to high trouble hours where 32.05% of working hours are used to solve production problems. The high trouble hours is caused by three factors, these are product trouble, process, and machine. The cause that mostly impact trouble hours is long sorting time with 1.76 hours average time. Rejected products can be divided into internal and external causes. The percentage of rejected products from external and internal causes are 0.51% and 3.99%, respectively. Internal rejected products occurred because of the broken material as 49%. 58% of it are caused by USW machine. The proposed improvement is given by updating the standard time.